Upaya Pancasila Dalam Pencegahan Hoax Di Sosial Media Terhadap Mahasiswa - Dhea Rivani Gultom; Ester Yolanda; Laura Sanulo Balaki Bago; Maria Isabel Sitinjak; Nadzifa Khalishah Salim Nst (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2023)
Social media users are dominated by the millennial generation who are familiar with digitalization. The millennial generation needs to be educated through Pancasila education, especially students, so they know the impact of spreading false information (hoaxes). The aim of this research is to determine student responses to the spread of false information (hoaxes) on social media. This research was conducted using quantitative methods through surveys using Google Form media to obtain respondents' answers, especially among students. As a result of 46 answers distributed on Google form, 39.8% of respondents were more interested in using Instagram, and 65.2% of respondents often read news on social media. All respondents used social media to look for news, but 87% of respondents did not believe it and 56.5% of respondents immediately looked for the truth. After reading it, 50% of respondents had spread it after 82.6% of respondents thought hoaxes were related to literacy. From all the data, students are more likely to look for facts from the news they read and they spread the news if the news contains truth.